Trends in birth attendants in Sudan using three consecutive household surveys (from 2006 to 2014) - Noon Altijani; Mustafa Khogali; Lisa Hinton; Charles Opondo; Eman Eljack; Marian Knight; Manisha Nair (Frontiers Media S.A., 2023)
IntroductionImproving maternal health and survival remains a public health priority for Sudan. Significant investments were made to expand access to maternal health services, such as through the training and deployment of providers with varying skills and competencies to work across the country. This study investigates trends in the coverage of different birth attendants and their relationship with the maternal mortality ratio (MMR).MethodsTrend analyses were conducted using data from the 2006, 2010, and 2014 Sudan Household surveys. Three categories of birth attendants were identified: (1) skilled birth attendants (SBA) such as doctors, nurse-midwives, and health visitors, (2) locally certified midwives, and (3) traditional birth attendants (TBA). Multivariable logistic regression models were used to examine trends in SBAs (vs. locally certified midwives and TBAs), locally certified midwives (vs SBAs and TBAs), and SBAs and locally certified midwives by place of birth (health facility and home). The analyses were adjusted for potential confounders. An ecological analysis was conducted to assess the relationship between birth attendants by place of birth and MMR at the state level.ResultsBirths by 15,848 women were analysed. Locally certified midwives attended most births in each survey year, with their contribution increasing from 36.3% in 2006 to 55.5% in 2014. The contributions of SBAs and TBAs decreased over the same period. In 2014 compared with 2006, births were more likely to be attended by a locally certified midwife (aOR: 2.19; 95%CI: 1.82-2.63) but less likely to be attended by a SBA (aOR: 0.46; 95%CI: 0.37-0.56). The decrease in SBA was more substantial for births taking place at home (aOR: 0.17; 95%CI: 0.12-0.23) than for health facility births (aOR: 0.45; 95%CI: 0.31-0.65). In the ecological analysis 2014-2016, the proportion of births attended by SBA in health facilities correlated negatively with MMR at state level (rho −0.55; p: 0.02).ConclusionThis analysis suggests that although an improved coverage of maternal health with locally certified midwives has been observed, it has not provided the skill level reached by SBA. SBAs working in facility settings were a key correlating factor to reduced maternal mortality. Urgent action is needed to improve access to SBAs in health facilities, thereby accelerating progress in reducing maternal mortality.